Vase life of cut Lilium pumilum inflorescences with salicylic acid - Santos, Mirelle Nayana; Tolentino, Márcia Martins; Mapeli, Ana Maria (Ornamental Horticulture, 2018)
The demand for flowers and ornamental plants has significantly increased in recent years. However, in most cases, the production of such species is accompanied by inappropriate postharvest handling, which is responsible for significant losses of marketed flowers. Lilium pumilum, a member of the family Liliaceae, is one of the ornamental species with economic potential as potted or cut flower, which features long stalks containing orange inflorescences with several flower buds and numerous smooth as well as linear leaves. Due the high perishability of this product, appropriate techniques that extend flower longevity should be employed. The present study was developed to evaluate the effect of salicylic acid (SA) on the postharvest preservation of L. pumilum inflorescences. Stalks were kept in maintenance solution with different concentrations of SA (0, 1, 5 and 10 mM) for 0, 6, 12, 18 and 24 h. The L. pumilum flowers had longevity decreased by 57.8 and 63.1% when kept in 5 and 10 mM SA, respectively, compared with control. This effect may be associated with the observed decrease in the percentages of flower opening and chlorophyll content as well as the damping-off of stalks, indicating phytotoxicity. Therefore, the use of 5 and 10 mM SA is inefficient to extend the longevity of L. pumilum.